(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In 2020 the Austrian Constitutional Court repealed a legal provision prohibiting assisted suicide. This essay deals with the Court’s decision and its consequences and focuses particularly on the new regulation on assisted suicide that entered into force in January 2022.